2019
DOI: 10.1021/acs.jafc.9b01253
|View full text |Cite
|
Sign up to set email alerts
|

d-chiro-Inositol Ameliorates High Fat Diet-Induced Hepatic Steatosis and Insulin Resistance via PKCε-PI3K/AKT Pathway

Abstract: d-chiro-Inositol (DCI) is a biologically active component found in tartary buckwheat, which can reduce hyperglycemia and ameliorate insulin resistance. However, the mechanism underlying the antidiabetic effects of DCI remains largely unclear. This study investigated the effects and underlying molecular mechanisms of DCI on hepatic gluconeogenesis in mice fed a high fat diet and saturated palmitic acid-treated hepatocytes. DCI attenuated free fatty acid uptake by the liver via lipid trafficking inhibition, redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…According to our data, DCI was able to rescue the deficiency of AKT activity (measured as activating phosphorylation) induced by DHT. As DCI has been also described in striate muscle [ 44 , 45 ], we speculate that if present in other tissues, DCI could restore the PI3k-AKT pathway and help counteract the effects of PCOS syndrome. Interestingly, other metabolic sensors such as mTOR were not noted to play a role in this response to DCI.…”
Section: Discussionmentioning
confidence: 52%
“…According to our data, DCI was able to rescue the deficiency of AKT activity (measured as activating phosphorylation) induced by DHT. As DCI has been also described in striate muscle [ 44 , 45 ], we speculate that if present in other tissues, DCI could restore the PI3k-AKT pathway and help counteract the effects of PCOS syndrome. Interestingly, other metabolic sensors such as mTOR were not noted to play a role in this response to DCI.…”
Section: Discussionmentioning
confidence: 52%
“…DCI activity as hypoglycemic agent was recently confirmed by a preclinical study [ 67 ] that highlighted a new mechanism of action of DCI to decrease gluconeogenesis in insulin-resistant hepatocytes. This effect occurs via PI3K/AKT/FOXO1-mediated inhibition of glucose-6-phosphatase and cytosolic phosphoenolpyruvate carboxykinase mRNA expression [ 67 ]. In the study, DCI was able to reduce hepatic gluconeogenesis and endogenous glucose consumption, not only in human HepG2 cells but also in insulin-resistant mice.…”
Section: Discussionmentioning
confidence: 98%
“…In the study, DCI was able to reduce hepatic gluconeogenesis and endogenous glucose consumption, not only in human HepG2 cells but also in insulin-resistant mice. The decreased gluconeogenesis accounts for DCI-induced lowering of blood glucose levels and amelioration of glucose homeostasis and insulin resistance (IR) [ 67 ]. Such finding increased the number of different mechanisms through which DCI counteracts peripheral IR, observed also in other experimental models where IR was induced by glucosamine [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our findings, we showed that DCI treatment was able to restore phosphorylation of the IR/IRS-1/AKT pathway in α-TC1-6 cells exposed to palmitate, ameliorating the insulin responsiveness of α-cells. Previous studies indicated that DCI can improve the insulin pathway by acting on the IR/AKT axis in hepatic and skeletal muscle tissues [ 27 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%